Feasibility Study for Biodiesel Production From Crude Palm Oil - Nor Adila, Said (2012)
Biodiesel is well known as fatty acid alkyl methyl esters. It is a fuel comprised of mono-alkyl esters of long chain fatty acids derived from vegetable oils, animal fats, or mixtures of vegetable oils and animal fats. It is produced by transesterification, with glycerol being produced as a by-product. Biodiesel is an environmentally friendly fuel which can be used in diesel engine without modification. Malaysia is a leading palm oil producers. Therefore, this study analyses the economic feasibility of producing palm oil based biodiesel in Malaysia in order to replace the diesel fuel consumption. The demand and cost production of palm oil biodiesel is estimated. It is found that the present price for biodiesel is RM 3.54 according to the optimum yield found in this study (88%) and this cost still consider high cost. But, in the future it might be considered reasonable price according to the market prices of fossil fuel and crude palm oil price. In current situation, Malaysia is sustaining all the challenges and issues. In future, palm biodiesel might be replaced with other feedstock diesel or biomass energy while palm diesel may face feedstock availability issue.